Training of general working physical skills of young adults with intellectual disabilities through an integrated physical capacity program - Dobrovolskytė, Ilona (Social Welfare: Interdisciplinary Approach, 2020)
The article describes a quasi-experiment that lasted 3 months and an integrated physical capacity training (IPCT) program, a diagnostic assessment of general working physical abilities using the Ergos IITM Work Simulator system. The results of the study reveal the impact of the IPCT program on the change of general work physical abilities and the assessment of subjective efforts of young adults with intellectual disabilities.